2013
DOI: 10.1371/journal.pone.0059536
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-Guided Intramural Inoculation of Orthotopic Bladder Cancer Xenografts: A Novel High-Precision Approach

Abstract: Orthotopic bladder cancer xenografts are essential for testing novel therapies and molecular manipulations of cell lines in vivo. Current xenografts rely on tumor cell inoculation by intravesical instillation or direct injection into the bladder wall. Instillation is limited by the lack of cell lines that are tumorigenic when delivered in this manner. The invasive model inflicts morbidity on the mice by the need for laparotomy and mobilization of the bladder. Furthermore this procedure is complex and time-cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 48 publications
(52 citation statements)
references
References 28 publications
0
50
0
Order By: Relevance
“…We then assessed growth as previously described [20, 21]. After 20 days, tumors derived from UMUC-3/shScr control cells reached an average of 200 mm 3 of tumor volume (Figure 7A); in contrast, the progranulin depleted UMUC-3/shPGRN showed a significantly reduced tumor growth (*** P < 0.001, Figure 7A).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We then assessed growth as previously described [20, 21]. After 20 days, tumors derived from UMUC-3/shScr control cells reached an average of 200 mm 3 of tumor volume (Figure 7A); in contrast, the progranulin depleted UMUC-3/shPGRN showed a significantly reduced tumor growth (*** P < 0.001, Figure 7A).…”
Section: Resultsmentioning
confidence: 99%
“…Briefly, 22 nine weeks old female athymic nude mice (NU-Foxn1 nu , Harlan Laboratories, Indianapolis, IN) with the average weight of 24.3 g were assigned into 2 groups by weight. Tumor inoculation was performed by ultrasound-guided injection according to the technique developed in our laboratories [20, 21]. Mice were anesthetized with 2.5% isoflurane plus meloxicam 1 mg/ Kg (Boehringer Ingelheim Vetmedica, St. Joseph, MO) subcutaneously.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, a urologic research group demonstrated successful percutaneous injection and ultrasound guidance of intramural orthotopic bladder cancer xenografts with consistent tumor engraftment in different cell lines. Furthermore, and of great interest, they were able to perform intratumoral injections in all mice of a control group, demonstrating the potential of these techniques for ultrasound-guided injections [23]. …”
Section: Discussionmentioning
confidence: 99%
“…Orthotopic murine xenograft muscle invasive bladder cancer model 13 All animal procedures were performed according to the guidelines of the Canadian Council on Animal Care (CCAC). The protocol was approved by the University of British Columbia animal care committee (protocol number A10-0192).…”
Section: Um-uc3 Luciferase-expressing Cellsmentioning
confidence: 99%
“…The protocol was approved by the University of British Columbia animal care committee (protocol number A10-0192). Briefly, five 10-week-old female athymic nude mice (Harlan Labs, Indianapolis, IN, U.S.) were anesthetized and UM-UC3 luciferase firefly-expressing cells were suspended in Matrigel ® (BD Biosciences, Mississauga, ON, Canada) and injected into the submucosa of the bladder wall via ultrasound guidance 13 ( Fig. 1A).…”
Section: Um-uc3 Luciferase-expressing Cellsmentioning
confidence: 99%